PEER ASSESSMENT IN TEACHING LEARNING PROCESS OF A WRITING CLASS (RETAIN, 2015)
Abstract This study aims to investigate the students’ ability to assess peer’s written work. Many studies found the advantages of peer assessment like the speed of students’ learning. On the other hand, many studies also found the disadvantages of peer assessment like poor quality feedback from the students. This study was designed in qualitative research. The students of X graders in one of Senior High School in Mojokerto were observed during class. The students’ grammar and vocabulary which was corrected by peer were analysed to answer first and second problem and the students’ response during interview was transcribed and interpreted to answer the third problem. The result of this study showed that most of the students faced some problems when conducting peer assessment in the writing class. The students did not acknowledge some grammatical errors and vocabulary errors in the students’ written works. The students also did not assess based on the grammar use and vocabulary use in descriptive text because the teacher did not give explanation about criteria of grammar and vocabulary that must be assessed by the students. Moreover, the students also gave good score to their peer without certain criteria of the score. In conclusion, the students faced some problems in assessing peer’s written work. The biggest problem found is the lack of student’s ability of sufficient knowledge. It makes the validity of peer assessment doubtfully to be used for measuring the students’ performance in this class. Keywords: Peer Assessment, Writing, Grammatical Error, Vocabulary Error Abstrak Penelitian ini bertujuan untuk meneliti kemampuan siswa dalam menilai tulisan teman sejawat. Banyak penelitian yang telah menemukan keuntungan dari penilaian teman sejawat, seperti kecepatan pemahaman siswa terhadap matapelajaran. Namun, ada juga penelitian yang menemukan bahwa penilaian oleh teman sejawat memunyai kekurangan, seperti kualitas masukan yang buruk dari siswa. Penelitian ini menggunakan metode kualitatif. Siswa kelas sepuluh MAN Mojokerto diteliti untuk mendapatkan beberapa data yang diperlukan. Struktur bahasa dan pemilihan kata dari tulisan siswa yang telah dikoreksi teman sejawat dianalisis untuk menjawab rumusan masalah pertama dan kedua. Kemudian, jawaban siswa dalam wawancara disalin dan dideskripsikan untuk menjawab rumusan masalah ketiga. Hasil dari penelitian ini menunjukkan, bahwa banyak siswa menemukan kesulitan dalam pelaksanaan penilaian teman sejawat. Siswa tidak mengenali beberapa kesalahan struktur bahasa dan pemilihan kata. Kemudian, siswa tidak menilai tulisan teman sejawat sesuai dengan ciri kebahasaan dari teks deskriptif. Selain itu, siswa juga memberi skor kepada teman sejawat tanpa pedoman kriteria penilaian. Hal-hal ini membuat hasil penilaian teman sejawat diragukan untuk mengukur kemampuan siswa. Sehingga, dapat disimpulkan bahwa siswa menghadapi beberapa kesulitan untuk menilai tulisan teman sejawat. Kesulitan terbesar siswa adalah kurangngnya pengetahuan yang dibutuhkan untuk menilai tulisan teman sejawat. Hal ini membuat kebenaran dari hasil penilaian teman sejawat diragukan untuk digunakan sebagai pedoman pengukuran kemampuan siswa di kelas tersebut. Kata Kunci: Penilaian Teman Sejawat, Penulisan, Kesalahan Struktur Bahasa, Kesalahan Kata